Analysis Of Personality, Achievement Motivation, And Work Spirit On Employee Work Discipline At PT Sapta Sentosa Jaya Abadi - Cut Dina Olivia; Eli Delvi Yanti; Daud Arifin (Journal of Management, Economic, and Accounting, 2026)
This study aimed to analyze the effect of personality, achievement motivation, and work enthusiasm on employee work discipline at PT Sapta Sentosa Jaya Abadi. The study used a quantitative approach with an associative method. The research population consisted of 47 employees, and the sample also comprised 47 respondents selected using a saturated sampling technique. Primary data were obtained through the distribution of questionnaires, and the results were processed using SPSS software version 24. Data analysis was conducted using multiple linear regression to examine the relationship between the independent variables and the dependent variable. The results showed that personality, achievement motivation, and work enthusiasm, both partially and simultaneously, had a positive and significant effect on employee work discipline. Personality had a regression coefficient of 0.282, a t-value of 2.919, and a significance value of 0.006. Achievement motivation had a regression coefficient of 0.207, a t-value of 2.540, and a significance value of 0.015. Work enthusiasm had a regression coefficient of 0.292, a t-value of 3.263, and a significance value of 0.002. Simultaneously, the F-value obtained was 73.224 with a significance value of 0.000. Work enthusiasm became the most dominant variable influencing work discipline, as it had the highest regression coefficient. The coefficient of determination (adjusted R²) of 0.825 indicated that 82.5% of the variation in work discipline was explained by personality, achievement motivation, and work enthusiasm. In addition, the strength of the relationship between the independent variables and the dependent variable was categorized as very strong, with a correlation coefficient (R) of 0.914.